Willem van Otterloo (1907-1978): een dirigentenloopbaan - Nelissen, Niek 1952- (Utrecht Van Gruting, 2009)
Willem van Otterloo was one of the four most important Dutch conductors of the 20th century. As a composer, he left behind a small but refined oeuvre. His best-known work is the Symphoniëtta (1943), which is among the most played Dutch compositions. Van Otterloo's life story gives an interesting snapshot of musical life between 1928 and 1978. He began his career as a tutti cellist in the Utrecht City Orchestra. A composition competition held by the Concertgebouw in 1932 proved decisive for his future. The orchestral suite he submitted was awarded first prize and he was allowed to conduct the performance by the Concertgebouw Orchestra itself. The USO appointed him second conductor in 1934 and first conductor in 1937. He stayed on when in 1943 the USO was assigned to the Europasender, a German propaganda station. This landed him a conviction by the Honour Council for Music after liberation. In 1949, Van Otterloo became first conductor of the Residentie Orkest, which he led for almost a quarter of a century. With him, the Hague orchestra entered an unprecedented heyday.In 1950, he became one of the permanent conductors of Philips' new record label, which had him record in Berlin, Paris and Vienna in addition to the RO.The many Philips LPs contributed to his international reputation. After the death of Eduard van Beinum in 1959, it was widely expected that he would be his successor at the Concertgebouw Orchestra. However, Bernard Haitink was chosen and Van Otterloo remained in The Hague.In the 1960s, Van Otterloo came under fire at the RO for calling for participation and repertoire renewal.As a guest conductor, he partly shifted his activities abroad.After leaving the RO in 1973, he became principal conductor of the Sydney Symphony Orchestra.In 1978, he died in Australia in a traffic accident. (Translated with Deepl.com)
Keywords: Otterloo, Willem van -- 1907-1978; Music history; Conductor; Biography